Morphological and physiological changes in Artemisia selengensis under drought and after rehydration recovery - Huang, Hui-Xiong; Cao, Yun; Xin, Kai-Jing; Liang, Rong-Hua; Chen, Yi-Ting; Qi, Jia-Jun (Frontiers in Plant Science, 2022)
Changes in global climate and precipitation patterns have exacerbated the existing uneven distribution of water, causing many plants to face the alternate situation of drought and water flooding. We studied the growth and physiological response of the wetland plant Artemisia selengensis to drought and rehydration. In this study, Artemisia selengensis seedlings were subjected to 32.89% (SD), 47.36 % (MD), 60.97% (MID), and 87.18 % (CK) field water holding capacity for 70 days, followed by 14 days of rehydration. The results showed that drought inhibited the increase of plant height, basal diameter, and biomass accumulation under SD and MD, but the root shoot ratio (R/S) increased. Drought stress also decreased the content of total chlorophyll (Chl), chlorophyll a (Chl-a), chlorophyll b (Chl-b), and carotenoid (Car). Soluble sugar (SS) and proline (Pro) were accumulated rapidly under drought, and the relative water content (RWC) of leaves was kept at a high level of 80%. After rehydration, the plant height, basal diameter, biomass, and R/S ratio could not be recovered under SD and MD, but these indicators were completely recovered under MID. The RWC, Chl, Chl-a, Chl-b, Car, and osmotic substances were partially or completely recovered. In conclusion, Artemisia selengensis not only can improve drought resistance by increasing the R/S ratio and osmotic substances but also adopt the compensatory mechanism during rehydration. It is predictable that A. selengensis may benefit from possible future aridification of wetlands and expand population distribution.